Quality Of Service Provisioning Scheme For Real-Time Applications in IEEE 802.11 Wireless Local Area Network - Ng, Roger Cheng Yong (2006)
This thesis presents a novel quality of service (QoS) provisioning scheme for realtime applications in IEEE 802.1 1e wireless local area networks (WLAN). The emerging 802.1 1e standard is tackling the exploding volume of traffic in WLANs with a long -term solution based on QoS-architectures. QoS delivers predictability and consistency into existing variability of best-effort delivery system offered in internet protocol (IP) and IEEE 802.11 wireless networks. Service differentiation in WLAN networks is achieved by means of assigning packets (from the network layer) to different access categories (AC), a set of fixed medium access control (MAC) level parameters that defines the priority echelon for each AC. Thus real-time applications are assigned higher priority ACs to ensure better service and to ensure that the delay constraints of these applications are promptly dealt with. An algorithm called Slide and Translate (SNT) is proposed for IEEE 802.1 1 WLANs. The SNT adapts contention parameters of individual ACs based on the network load in a basic service set (BSS). SNT is derived from the observations of the success and failures of previously proposed QoS provisioning schemes. The SNT adapts the backoff interval, minimum contention window (CW,,,) and contention offset (CWOffsetto) ensure the QoS constraints for the different ACs are dealt with. To further understand the SNT, a simple mathematical analysis is presented on the inter-AC differentiation characteristics; subsequently, through simulation it is shown that SNT is able to maintain high medium utilisation over a wide range of offered loads while providing a high degree of isolation (in terms of throughput, delay and frame loss) to high priority traffic. Further to this, an extension to the SNT called SNT-AC is proposed in order to achieve efficient end-to-end resource provisioning. SNT-AC uses an admission control algorithm to restrict flows in and out of the BSS. The admission controller resides in the IP layer and makes decision based on the MAC level feedback. The simulation results indicate that the close coupling QoS coordination can ensure both bandwidth and latency to admitted flows by controlling the effective offered load into the BSS. This guarantees high priority ACs protection against overwhelming traffic in a WLAN. Finally a brief discussion on future directions of WLANs and hardware implementation issues conclude the thesis.